2023
DOI: 10.3390/polym15030731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrospinning Setup Parameters on Properties of Polymer-Perovskite Nanofibers

Abstract: Optimizing the properties of electrospun polymer-perovskite nanofibers is considered essential for improving the performance of flexible optoelectronic devices. Here, the influence of electrospinning setup parameters (i.e., electrical voltage, collector type (planar or rotary), rotation speed, as well as process time) on the properties (i.e., external structure, perovskite crystallinity, optical properties, thermal properties, the shrinkage ratio, mechanical properties, and long-term stability) of electrospun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…4. This shows that high porosity nano bers have higher nano ber diameter correlated well with literature [40].…”
Section: Sem Analysissupporting
confidence: 90%
“…4. This shows that high porosity nano bers have higher nano ber diameter correlated well with literature [40].…”
Section: Sem Analysissupporting
confidence: 90%
“…It has been demonstrated that the electrospinning process is an efficient method for the production of fibers that possess exceptional qualities. Researchers have found that the diameter control, morphology, and alignment of the fibers can be changed by adjusting the parameters of the electrospinning setup [ 30 , 31 ]. These parameters include the voltage, the distance between the spinneret and the collector, and the flow rate of the polymer solution.…”
Section: The Nanofibers and Electrospinning Methodsmentioning
confidence: 99%
“…Physical blending of MHP nanocrystals (NCs) with a plethora of polymer solutions, such as PMMA, PS, poly(styrene-ethylene-butylene-styrene) (SEBS), and poly(lauryl methacrylate) (PLMA), has been explored to form nanocomposite materials with enhanced stability and processability for PV devices [92,94]. Many MHP-polymer nanocomposites are prepared through modified spin-coating approaches to produce films with uniform size, thickness, and morphology [74,85,94,95]. Physical blending has been viewed as a simple, effective, and scalable technique for the large-scale commercialization of MHP-polymer nanocomposites.…”
Section: Blending Polymers With Mhp Nanocrystalsmentioning
confidence: 99%